Rehabilitasi Mangrove Berbasis Partisipatif dan Pembelajaran Konservasi di Kelurahan Bungkutoko, Kota Kendari - Abdul Hamid; Syamsul Kamri; Andi Nur; Romy Ketjulan; Halili; Ermayanti Ishak; Rahmad Patadjai; Adi Wahyudi (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Mangrove rehabilitation is an important strategy to restore the ecological and social functions of urban coastal areas affected by land use conversion, reclamation, infrastructure development, and settlement expansion. This article aims to present and analyze participatory-based mangrove rehabilitation and conservation learning in Bungkutoko Village, Kendari City. This activity was carried out from April to June 2025. This series of activities included coordination, observation of potential rehabilitation sites, preparation of seedlings and sowing seedlings, planting seedlings, and socialization and field reflection. A total of 100 Rhizophora mucronata seedlings were planted in the degraded area with a planting distance of approximately 1 x 1 m, and involved approximately 50 students along with lecturers, and village officials. Participatory-based mangrove rehabilitation and conservation learning are one strategy to maintain the sustainability of the mangrove ecosystem in Bungkutoko Village, and this activity not only focuses on planting mangrove seedlings, but also builds student awareness to participate in maintaining and preserving mangroves sustainably.